2021
DOI: 10.1111/nin.12412
|View full text |Cite
|
Sign up to set email alerts
|

Can nursing educators learn to trust the world’s most trusted profession?

Abstract: Nursing and nursing education face a paradox whereby the world's most trusted profession seems not to trust its own students and practitioners. Much of nursing education has adopted what has been memorably described as the 'cop shit' approach. This is the panoply of surveillance, anti-plagiarism and proctoring technologies that appear to be used more for policing and punishment of an inherently dishonest student body than to develop ethical and scholarly writing among future peers and colleagues.Nurses in prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…Yet more often, technological innovations that could facilitate transformational advancements in accessibility instead get used for surveillance and punishment. Activist scholars have accurately referred to such practices as "cop shit" (Darbyshire & Thompson, 2021). The use of sophisticated digital technologies to moni-tor and sanction people appears widely throughout capitalist societies, with nuances specific to unique work contexts such as university education (Wan & Albracht, 2021).…”
Section: On "Cop Shit"mentioning
confidence: 99%
“…Yet more often, technological innovations that could facilitate transformational advancements in accessibility instead get used for surveillance and punishment. Activist scholars have accurately referred to such practices as "cop shit" (Darbyshire & Thompson, 2021). The use of sophisticated digital technologies to moni-tor and sanction people appears widely throughout capitalist societies, with nuances specific to unique work contexts such as university education (Wan & Albracht, 2021).…”
Section: On "Cop Shit"mentioning
confidence: 99%
“…Robust discussion in higher education literature has demonstrated that such technologies invade privacy and as such are a form of violence. 31 , 32 , 33 , 34 These technologies have also been demonstrated to lack impact on learning, as the multiple choice exams they often accompany are a poor marker of understanding. 35 , 36 As a profession, embracing this opportunity to step away from standardized testing models to those that allow students to demonstrate understanding in other ways would be an excellent step forward.…”
Section: Tic Assumptions and Guiding Principlesmentioning
confidence: 99%
“…These requirements create both a ranked system of privilege and a significantly isolating situation for students. That these strict policies focused on both controlling many aspects of students’ actual behavior and inclusion of policing the “appearance of violations” demonstrates an important lack of trust in students’ ability to make reasonable choices 31 …”
Section: Tic Assumptions and Guiding Principlesmentioning
confidence: 99%
“…In order to shift toward authentic assessment, nurse educators need to learn to trust students. Darbyshire and Thompson14 argue that educators must stop policing students because learning to trust students is also essential for the future of nursing. Nursing is founded on trust 9.…”
Section: Critical Caring Pedagogy and Nursing Educationmentioning
confidence: 99%
“…Then, educators need to learn to trust students. 14 Once trust is established, a shift toward more authentic forms of assessment can be made. Educators are encouraged to (1) identify measurable learning outcomes that are connected to real-world practice settings; (2) consider the context that nurses in the real-world need to use the testable material in; (3) design exams that require reflection and critical thought to answer; (4) use the same time, collaboration, and surveillance limitations as the real-world setting; (5) provide students with feedback on their performance; and (6) when cheating occurs, help everyone involved learn from the incident.…”
Section: E141mentioning
confidence: 99%